Linggui Zhugan Decoction activates the SIRT1-AMPK-PGC1α signaling pathway to improve mitochondrial and oxidative damage in rats with chronic heart failure caused by myocardial infarction - Yu, Siyi; Qian, Hang; Tian, Dawei; Yang, Mingming; Li, Dongfeng; Xu, Hao; Chen, Jishun; Yang, Jingning; Hao, Xincai; Liu, Zhixin; Zhong, Jixin; Yang, Handong; et al. (Frontiers in Pharmacology, 2023)
Objective: To investigate the effects of Linggui Zhugan Decoction on mitochondrial and oxidative damage in rats with chronic heart failure after myocardial infarction and the related mechanisms Methods: Chronic heart failure after myocardial infarction was established by coronary artery ligation. Heart failure rats were randomly divided into three groups: model group (n=11), Linggui Zhugan Decoction group (n=12) and captopril group (n=11). Rats whose coronary arteries were only threaded and not ligated were sham group(n=11). Cardiac function, superoxide dismutase (SOD), malondialdehyde (MDA) contents, soluble growth-stimulating expression factor (ST2), and N-terminal B-type brain natriuretic peptide precursor (NTproBNP) levels were analyzed after treatment. Moreover, the level of mitochondrial membrane potential was detected by JC-1 staining, the ultrastructural of myocardial mitochondria were observed by transmission electron microscopy. The related signal pathway of silent information regulator factor 2-related enzyme 1 (SIRT1), adenylate activated protein kinase (AMPK), phosphorylated adenylate activated protein kinase (p-AMPK), and peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) is an important pathway to regulate mitochondrial energy metabolism, and to initiate mitochondrial biogenesis. The expression level was detected by Western blot and reverse transcription to explore the mechanism of the decoction. Results: Compared with the model rats, Linggui Zhugan Decoction significantly improved cardiac function (P<0.05), reduced MDA production (P<0.01), increased SOD activity (P<0.05), reduced ST-2(P<0.01) and NT-proBNP(P<0.05) levels, increased mitochondrial membrane potential, and improved mitochondria function. In addition, Linggui Zhugan Decoction up-regulated the expression of SIRT1, p-AMPK, PGC-1α protein, and mRNA in cardiac myocytes. Conclusions: Linggui Zhugan Decoction can improve the cardiac function of heart failure rats by enhancing myocardial antioxidant capacity and protecting the mitochondrial function, the mechanism is related to activating SIRT1/AMPK/PGC-1α signaling pathway.